REVIEW: THE USE OF TOFU RESIDUE IN THE PHARMACEUTICS - Ine Suharyani; Iin Indawati; Encu Asep Setiadi; Maisya Mauliana Insani; Ibnu Mas'ud (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
Tofu is a processed soy product consisting of soft solids made by clumping soy protein extracts. The residual result of tofu processing is called the tofu dredging waste. In Indonesia, tofu waste remains an unsolved problem. Many people argue that the waste from tofu processing (tofu residue waste) does not have high economic value and is only used as feed for livestock and is even thrown carelessly into the river, which causes damage to the ecosystem. Tofu pulp has high nutritional content, such as protein (26.6%), fat (18.3%), carbohydrates (41.3%), phosphorus (0.29%), calcium (0.19%), iron (0.04%), and water (0.09%). The purpose of this journal review is to determine the use of tofu residue waste and solve the problem of tofu residue waste in the community. The method used was collecting various research journals through the Google Scholar website with keywords for the use of tofu residue in the pharmaceutical field. Based on the 7 journals reviewed, tofu pulp can be used as an anti-aging, adsorbent, anti-diabetes, anti-inflammatory, bioethanol, and excipient in tablet production. Keywords: Tofu, tofu residue, pharmaceutical